The genus Nereis L., 1758 (Polychaeta, Nereididae); state of the art for identification of Mediterranean species - Gravina, Maria Flavia; Lezzi, Marco; Bonifazi, Andrea; Giangrande, Adriana (Atti della Società Toscana di Scienze Naturali, Memorie, 2015)
The existence of critical problems in the identification of species within the genus Nereis L., 1758 (Annelida Polychaeta: Nereididae) has led to several misidentifications within Mediterranean taxa. In the present paper we report a discussion on the Mediterranean species, with a re-examination of specimens collected along the Italian coasts. A redescription of each species is provided, pinpointing the diagnostic characters with detailed figures for easy identification. Old and recent synonymies are also discussed and a key for identification is provided
World Polychaeta Database (WPolyDb)